THE MEANING AND CHARACTERISTICS OF ISLAM IN THE QUR'AN - H., Baharuddin Husin; H., Supriyatin; Zaimudin,; Zabidi, Imron (International Journal of Psychosocial Rehabilitation, 2020)
Islam contain the meaning of submissiveness and total surrender to Allah SWT and to all His rules that have been revealed to His chosen Prophet, Muhammad (PBUH). Islam is a religion of nature, because Islam is something that is inherent in human beings and has been brought from birth through the nature of Allah’s creation, means that humans from the beginning have a religious instinct of monotheism (tawheed). Islam in accordance with its characteristics, is like a perfect building with a strong foundation of faith and pillar joints in the form of worship to Allah SWT and beautified with noble morals. While the regulations in the Shari'ah function to strengthen the building. While true da'wah and jihad are the fences which guard against the damage done by the enemies of Islam. Islam pays attention to worldly and ukhrawi balance. Islam describes a wholeness and unity in all aspects. Paying attention to peace, optimism in achieving happiness in life, managing personal life, family, society, country and the world as a whole. Set all the creations of Allah SWT in this nature to return to His law. Islam is the eternal religion of Allah SWT that was revealed to the Prophet Muhammad (PBUH). All previous celestial teachings are the unity of the divine teaching in various forms which are constantly updated in accordance with the development of the times, the world, humans, and the demands of preaching at that time. The teachings of Islam brought by the Prophet Muhammad (PBUH) is the last phase as well as the peak of all celestial teachings revealed on the face of the earth (Surah Al Baqarah/2: 132; Surah Al-Ahzab: 40; Al Maidah/5: 3).